High-temperature degradation of the in-situ laser-glazed plasma sprayed LaMgAl11O19 thermal barrier coating exposed to Ca-Mg-Al-silicate deposits. (November 2020) - Sun, Yiwei; Wu, Hengkai; Zhao, Hongxu; Chen, Xiaolong; Guo, Chaoqian; Sun, Junbin; Cao, Xueqiang; Deng, Chunming; Li, Wei
Highlights: Dense columnar LaMgAl11 O19 (LaMA) sealing layer is in-situ created by laser-glazing. Dense columnar LaMA layer shows good interface compatibility and thermal stability. In-situ generated dense LaMA layer exhibits much better CMAS resistance at 1350 °C. La, Mg and Al from the dense LaMA layer arrest the melted CMAS very effectively. Abstract: High-temperature degradation of the plasma sprayed LaMA coating before and after in-situ laser-glazing under CMAS attacks at 1350 °C for 1 h, 12 h and 48 h was comparatively investigated. Results indicate that a dense laser-glazed top layer was successfully created in-situ for a ～1 mm thick LaMA coating. It behaved as a sealing layer and reservoir of Al 3+, Mg 2+ and La 3+ . Melted CMAS penetration was accordingly effectively arrested accompanied by crystallizations of the CaAl2 Si2 O8 anorthite, MgAl2 O4 spinel and Ca2 La8 (SiO4 )6 O2 apatite. CMAS-induced degradation mainly occurred near the surface of the laser-glazed dense LaMA top layer. While significant penetration of the melted CMAS along the entire thickness occurred to the as-sprayed LaMA coating without laser-glazing treatments after 48 h degradation. Ca2 La8 (SiO4 )6 O2 apatite phase did not crystallize for the as-sprayed LaMA due to the much reduced local La 3+ concentration in melted CMAS resulted from its porous microstructure. Effects of laser-glazing on the CMAS-induced degradation of the plasma sprayed LaMA was carefully analyzed and discussed in terms of the coating's chemical composition, microstructure and surface physical chemistry characteristics base on XRD, SEM/EDS and TEM results.